Measuring Readiness to Welcome a Golden Indonesia (2045): Analysis of the Implementation of Pancasila Economics and its Legal Umbrella - Alfiani, Novita; Al Akhdloriy, Abdurrahman; Mawardi, Chalik (Jurnal Legisci, 2024)
A factor that can support the accomplishment of the Indonesian state's objectives is the economic application of Pancasila. From Mohammad Hatta's worldview, the Pancasila economy is a force that can support the accomplishment of national objectives. To attain national objectives, create a modern, wealthy, and prosperous Indonesia. Normative legal research is what this study is. According to the research, cooperatives have Pancasila economic values and are vital to the country's economy. A more appropriate reflection of the family-based and Pancasila-based economic system model of economic law development can be seen in creating cooperatives to address issues that provide difficulty for foreign investment. In order to fulfill the dream of Indonesia's golden years, it can significantly influence the country's economic growth in 2045.